Vicinal dianions of diethyl α-aroylsuccinates: Preparation of functionalized-2,3-dihydrofurans and -furans, and diaxial 2,4-diaryl-3,7-dioxabicyclo[3.3.0]octanes - Manat Pohmakotr (2018)
Vicinal dianions of diethyl α-aroylsuccinates react with aromatic aldehydes to provide functionalized 2,3-dihydrofurans as the major products together with γ-butyrolactones after treatment of the adducts obtained with a catalytic amount of p-toluenesulfonic acid in refluxing toluene. cis-2,3-Dihydrofurans are used as precursors for the preparation of tetrasubstituted furans and diaxial 2,4-diaryl-3,7-dioxabicyclo[3.3.0]octanes. © 2003 Published by Elsevier Ltd.